On new emerging concepts of modeling petroleum digital ecosystems by multidimensional data warehousing and mining approaches - Nimmagadda, Shastri; Dreher, Heinz; Nawaz, M.; Laiq, K. (IEEE, 2010)
Petroleum system and its ingredients are narrated for each and every oil and gas field in each and everypetroleum-bearing sedimentary basin. A new concept of ecosystem and its digitization are emerging within the generic petroleum system. Significance of this concept is to make connectivity among petroleum systems through attributes of ingredients and their contextualization and specification. Most popularly known ingredients are geological structure, reservoir, source and seal rocks. Other ingredients involved are in the form of process of these ingredients such as maturation (of source rocks) and migration and timing (of formation of structure, reservoir and seal rocks). One can notice the connectivity among primary petroleum system ingredients, through different processes, such as maturation of source rocks and charging capability and migration of hydrocarbons into suitablestructural (structure) entrapment areas of reservoir. Unless the phenomenon of interconnectivity is understood; integration between ingredients and processes in the context of digital representation and visualization, petroleum system existence and its survival cannot be well explained. Its value cannot beadded in terms of petroleum accumulations and volumes, unless these phenomena are explicit. Authors propose ontology based data warehousing and data mining technologies, in which, conceptualization and contextualization of multiple data dimensions (petroleum system?s ingredients and processes), integration (within data warehouse environment) and data mining of interpretable emerging petroleum digital ecosystems are accomplished. Multidimensional data warehousingand mining facilitate an effective interpretation of petroleum systems, minimizing the ambiguities involved during structure and reservoir qualifications and quantifications.